LOCALITY CONDITIONS AS A FACTOR OF GRAPE QUALITY IN ORGANIC AND CONVENTIONAL PRODUCTION - Ranković-Vasić, Zorica; Selić, Jelena; Vujadinović Mandić, Mirjam; Vuković Vimić, Ana (ACADEMIC REVIEW, 2021)
The aim of this work was to examine climatic characteristics and meteorological factors as their influence on the quality of grapes in the following varieties: Prokupac, Tamjanika bela, Smederevka and Lisičina, which were grown according to the principles of ecological production in the first year of conversion and in conventional production. The characteristics of the Požarevac vineyard area where the trial was conducted were determined through the analysis of bioclimatic indices and meteorological conditions in the year of the trial (2020) and over a multi-year period (2000-2019). The vegetation period in the examined year lasted longer (216 days) and had a higher amount of precipitation (486.3 mm), while in the multi-year period the length of the vegetation was 205.7 days with an amount of precipitation of 437.9 mm. In terms of grape quality, a difference was observed between the varieties and the interaction between the varieties and the production system.